Regional comparison of efficacy and safety for vilobelimab in critically ill, invasively mechanically ventilated COVID-19 patients - Gernot Marx; Antoine Roquilly; Tobias Welte; Jean Dellamonica; Greet Hermans; Martin Witzenrath; Michael Bauer; Matthias Gründling; Ulrich Jaschinski; Robert Zerbib; Djillali Annane; Matthijs C Brouwer; et al. (BMJ Open Respiratory Research)
Background Vilobelimab, a first in class C5a-specific monoclonal antibody, improved 28-day and 60-day mortality in intubated COVID-19 patients in PANAMO, a phase 3 randomised, double-blind, placebo-controlled multicentre study. All-cause mortality was pre-specified to be analysed pooling by region (western Europe, South America, South Africa/Russia).Methods Critically ill, invasively mechanically ventilated COVID-19 patients were randomised in a 1:1 ratio within 48 hours of intubation to receive vilobelimab treatment (six, 800 mg intravenous infusions) or placebo on top of standard of care. We analysed the efficacy and safety of vilobelimab based on prespecified geographic regions.Results 368 patients were randomised and analysed: 177 in the vilobelimab group and 191 in the placebo group. In western Europe (n=209), 28-day all-cause mortality was significantly lower in the vilobelimab group (21%) compared with placebo (37%) (HR 0.51 (95% CI: 0.30, 0.87), p=0.014). In South America (n=126), mortality was similar between groups (40% vs 37%; HR 0.94 (95% CI: 0.53, 1.67), p=0.83). In South Africa/Russia (n=33), mortality was 69% in the vilobelimab group and 87% in the placebo group (HR 0.62 (95% CI: 0.28, 1.38), p=0.25). Within the Brazilian subpopulation (n=74), a significant age imbalance between the vilobelimab and placebo group was detected (median 53.5 years in the vilobelimab group vs 44.5 years in the placebo group). Occurrence of treatment-emergent adverse events between regions was similar.Conclusion The most apparent 28-day all-cause mortality benefit for vilobelimab was in western Europe. Age imbalance between treatment groups in Brazil may have resulted in a lower efficacy signal for vilobelimab in South America compared with other regions. Overall, vilobelimab demonstrated a favourable safety profile and reduced mortality in critically ill, intubated COVID-19 patients, with regional variations influencing outcomes.